COMPARISON OF SAFETY AND EFFICACY OF ORAL PIOGLITAZONE VERSUS ORAL METHOTREXATE IN THE MANAGEMENT OF PATIENTS WITH PLAQUE-TYPE PSORIASIS: A RANDOMIZED CONTROL STUDY - Dr. Varshita Suresh Mendon; Dr. Vinay. K.N; Dr. Suresh M.R; Dr. Ravikumar B.C; Dr. Vivekananda Ittigi; Dr. Umadevi H.R (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Psoriasis is a chronic, immune-mediated inflammatory skin disorder affecting quality of life. Plaque-type psoriasis, its most common form, requires long-term management balancing efficacy and safety. Methotrexate, while effective, presents risks such as hepatotoxicity and hematological side effects. Pioglitazone, a thiazolidinedione, has shown potential as a safer alternative, but evidence remains inconclusive. Thus, the study aimed to compare the safety and efficacy of oral Pioglitazone versus oral Methotrexate in patients with plaque-type psoriasis. Materials & Methods: The study was conducted on plaque psoriasis patients at Hassan Institute of Medical Sciences. It followed an open-label randomized control design with 34 participants, split into two groups of 17 each. Group 1 received Methotrexate (7.5 mg) weekly with folic acid, while Group 2 received Pioglitazone (30 mg) daily. PASI scores were measured at baseline and reassessed at weeks 4, 8, and 12. Appropriate tests were performed to assess potential adverse events. Results: Methotrexate patients had a mean age of 56.12 years versus 50.76 years for pioglitazone (p = 0.177). Both groups had similar gender distributions (p = 0.697), illness duration (p = 0.914), and nail involvement (p = 0.486). Baseline PASI scores were 15.36 for methotrexate and 14.32 for pioglitazone, decreasing to 5.42 and 6.32 respectively by week 12 (p = 0.033). Methotrexate showed a 68.15% PASI improvement, while pioglitazone had 57.03% (p = 0.021). Six patients in the methotrexate group experienced adverse effects, compared to only three in the pioglitazone group (p = 0.117). Conclusion: Although methotrexate demonstrated superior efficacy in treating plaque-type psoriasis compared to pioglitazone, the pioglitazone group had a lower incidence of side effects. However, the difference in the adverse effect profiles between the two groups was not statistically significant.